Are active labour market policies effective in activating and integrating low-skilled individuals? An international comparison - Verónica Escudero (IZA Journal of Labor Policy, 2018)
This paper examines the effectiveness of active labour market policies (ALMPs) in improving labour market outcomes, especially of low-skilled individuals, by means of a pooled cross-country and time series database for 31 advanced countries during the period 1985-2010. The analysis includes aspects of the delivery system to see how the performance of ALMPs is affected by different implementation characteristics. Among the notable results, the paper finds that ALMPs matter at the aggregate level, but mostly through an appropriate management and implementation. In this regard, sufficient allocation of resources to programme administration and policy continuity appear to be particularly important. Moreover, start-up incentives and measures aimed at vulnerable populations are more effective than other ALMPs in terms of reducing unemployment and increasing employment. Interestingly, the positive effects of these policies seem to be particularly beneficial for the low skilled.
Keywords: J08; E24; H5; J68; D78; 330; Active labour market policies; Implementation; Unemployment rate; Low skilled; OECD; Aggregate effects